2020
DOI: 10.3389/fsufs.2020.547826
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Implications of Plant Secondary Metabolites - Phytochemical Diversity Can Enhance Agricultural Sustainability

Abstract: Conventional agriculture production, although proficient in feeding an expanding human population, is having negative environmental impacts that are diminishing the sustainability of natural resources. Producers and consumers are increasingly interested in understanding how land management practices can enhance agricultural sustainability and improve human health. This perspective article offers a new approach to enhancing agricultural sustainability by growing crops and forages with diverse plant secondary me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 119 publications
(138 reference statements)
1
19
0
Order By: Relevance
“…Natural products are successfully used in cosmetic, phytotherapy, and food-additive applications [ 44 ]. Plant secondary metabolites (e.g., terpenes, flavonoids, phenolic and polyphenolic compounds, nitrogen-containing and sulphur-containing compounds) also play a significant ecological role in crop defence (against, for example, bacteria, fungi, herbivores, plants, viruses), attraction and stimulation (e.g., nutrient sequestration, pollination), and counter abiotic stresses [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural products are successfully used in cosmetic, phytotherapy, and food-additive applications [ 44 ]. Plant secondary metabolites (e.g., terpenes, flavonoids, phenolic and polyphenolic compounds, nitrogen-containing and sulphur-containing compounds) also play a significant ecological role in crop defence (against, for example, bacteria, fungi, herbivores, plants, viruses), attraction and stimulation (e.g., nutrient sequestration, pollination), and counter abiotic stresses [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary plant constituents (e.g., sugars, proteins, amino acids, chlorophyll, and purines and pyrimidines of nucleic acids) are principally nutritional substances of plants and, in most cases, do not possess medicinal properties. Secondary plant constituents (secondary metabolites) such as alkaloids, carotenoids, flavonoids, glycosides, lignans, phenolic compounds, terpenoids, saponins, steroids, and tannins are accountable for multifarious biological, ecological, pharmacological, and toxicological activities [ 3 , 8 , 9 , 11 , 18 , 19 ]. Most of these secondary metabolites have a role in the defence against environmental factors (e.g., pollution, drought, UV light, pathogens) [ 3 , 19 ] and can be found in plants either permanently or only at certain stages of their growth [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of animals' productivity, animals that ingest forages containing different plants secondary metabolites get their meat and dairy products enhanced in terms of biochemical richness making them good for human consumption [93].…”
Section: The Role Of Secondary Metabolites In Enhancing Agricultural ...mentioning
confidence: 99%
“…Similarly, pyrethrins, azadirachtin and limonoids have strong insect deterrent ability and are commercially produced and used in agricultural systems (Clemensen et al, 2020). Besides the functions of these SM in plants in their natural environments, thanks to science, most of these SM are being induced in plants by external applications or used in industry to produce insecticides, herbicides, aromas, gums, cosmetics, flavour enhancers, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most of these SM has been used in the pharmaceutical industry due to their scientifically confirmed health benefits (Mendoza & Silva, 2018). Clemensen et al (2020) identify SM as agents responsible for communication among plants and their environment. They also reported that a better understanding of SM and their roles in agroecology would be beneficial for reducing the negative environmental impacts.…”
Section: Introductionmentioning
confidence: 99%